Persistent phosphorylation at specific H3 serine residues involved in chemical carcinogen‐induced cell transformation. Issue 5 (12th January 2017) - Zhu, Xiaonian; Li, Daochuan; Zhang, Zhengbao; Zhu, Wei; Li, Wenxue; Zhao, Jian; Xing, Xiumei; He, Zhini; Wang, Shan; Wang, Fangping; Ma, Lu; Bai, Qing; et al.
Abstract : Identification of aberrant histone H3 phosphorylation during chemical carcinogenesis will lead to a better understanding of the substantial roles of histone modifications in cancer development. To explore whether aberrant H3 phosphorylation contributes to chemical carcinogenesis, we examined the dynamic changes of H3 phosphorylation at various residues in chemical carcinogen‐induced transformed human cells and human cancers. We found that histone H3 phosphorylation at Ser10 (p‐H3S10) and Ser28 (p‐H3S28) was upregulated by 1.5‐4.8 folds and 2.1‐4.3 folds, respectively in aflatoxin B1 ‐transformed hepatocytes L02 cells (L02RT‐AFB1 ), benzo(a)pyrene‐transformed HBE cells (HBERT‐BaP), and coke oven emissions‐transformed HBE cells (HBERT‐COE). The ectopic expression of histone H3 mutant (H3S10A or H3S28A) in L02 cells led to the suppression of an anchorage‐independent cell growth as well as tumor formation in immunodeficient mice. In addition, an enhanced p‐H3S10 was found in 70.6% (24/34) of hepatocellular carcinoma (HCC), and 70.0% (21/30) of primary lung cancer, respectively. Notably, we found that expression of H3 carrying a mutant H3S10A or H3S28A conferred to cells the ability to maintain a denser chromatin and resistance to induction of DNA damage and carcinogen‐induced cell transformation. Particularly, we showed that introduction of a mutant H3S10A abolished the bindings of p‐H3S10 to the promoter of DNA repair genes, PARP1 and MLH1 upon AFB1 treatment. Furthermore, we revealed that PP2A was responsible for dephosphorylation of p‐H3S10. Taken together, these results reveal a key role of persistent H3S10 or H3S28 phosphorylation in chemical carcinogenesis through regulating gene transcription of DNA damage response (DDR) genes.